Analysis of the Influence of Non-Directional Algorithms on Fingerprint Image Enhancement - Kocevar, M.; Klampfer, S.; Chowdhury, A.; Kacic, Z. (Elektronika ir Elektrotechnika, 2014)
Fingerprint image enhancement is of key importance for the efficiency of the automated fingerprint identification system. Before we can enhance a fingerprint image with contextual filters, we need to enhance fingerprint image contrast and readability with non-directional filters. This article provides an analysis of the influence of non-directional image enhancement techniques in the fingerprint image pre-processing step. To perform the analysis we used global normalization algorithm, local normalization algorithm, Wiener filter, histogram equalization algorithm and median filter. To evaluate the equal error rate in the experiments, done on a public database FVC_2004, we used Gabor filter and a state-of-the-art two-stage algorithm. DOI: http://dx.doi.org/10.5755/j01.eee.20.6.7277